2015
DOI: 10.1037/xap0000061
|View full text |Cite
|
Sign up to set email alerts
|

Goal-oriented training affects decision-making processes in virtual and simulated fire and rescue environments.

Abstract: Decisions made by operational commanders at emergency incidents have been characterized as involving a period of information gathering followed by courses of action that are often generated without explicit plan formulation. We examined the efficacy of goal-oriented training in engendering explicit planning that would enable better communication at emergency incidents. While standard training mirrored current operational guidance, goal-oriented training incorporated "decision controls" that highlighted the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 23 publications
1
38
0
Order By: Relevance
“…This is a limitation of Study 1. However, the close correspondence between decision‐making processes in some operational and simulated environments, identified using similar methodology to the present studies (Cohen‐Hatton et al, ; Cohen‐Hatton & Honey, ), suggests that use of context appropriate simulated environments can reveal important similarities to real incidents (Alison et al, ). Of more immediate relevance, however, is the close similarity between the overall pattern of results from Study 1 (involving Exercise Wales Gold 1 and 2) and Study 2 (Exercise Unified Response; Figure ).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…This is a limitation of Study 1. However, the close correspondence between decision‐making processes in some operational and simulated environments, identified using similar methodology to the present studies (Cohen‐Hatton et al, ; Cohen‐Hatton & Honey, ), suggests that use of context appropriate simulated environments can reveal important similarities to real incidents (Alison et al, ). Of more immediate relevance, however, is the close similarity between the overall pattern of results from Study 1 (involving Exercise Wales Gold 1 and 2) and Study 2 (Exercise Unified Response; Figure ).…”
Section: Discussionsupporting
confidence: 75%
“…One obvious target is to modify policy and guidance to ensure that (a) options and contingencies are consistently explored, and (b) the rationale for prospective courses of action are routinely and explicitly assessed against goals, anticipated consequences, and a risk/benefit analysis (cf. Cohen‐Hatton & Honey, ). Cohen‐Hatton and Honey () showed that training firefighters to use such explicit assessments (which they called “decision controls”), before committing to a course of action, increased the use of reflective decision‐making relative to recognition‐primed or intuitive decision‐making.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The environment was manipulated using two virtual environments (see also Moskaliuk et al, 2017 ). Virtual environment technologies are useful tools for psychological research, as they are able to create sufficiently realistic situations while being able to control for confounding variables ( Blascovich et al, 2002 ) and have already been applied in various research areas (e.g., Cho et al, 2002 ; Klinger et al, 2005 ; Slater, 2009 ; Cohen-Hatton and Honey, 2015 ). In the work environment condition, participants navigated through a virtual office environment.…”
Section: Methodsmentioning
confidence: 99%